2002
DOI: 10.1038/sj.jp.7210794
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Group B Streptococcus Prevention Policy at a Community Hospital

Abstract: Over 90% of GBS-positive mothers were treated with antibiotics at WHG. Associated with this high adherence rate to the CDC guidelines has been a five-fold decrease in the incidence of EOGBS disease. We attribute these results to the implementation of a preprinted physician order sheet to direct intrapartum antibiotics for women with GBS positive or unknown colonization and the use of a clinical pathway to track GBS colonization status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We identified six studies that evaluated interventions to improve healthcare quality for neonates in community hospitals; two involved telemedicine 43‐48 . Hall et al described “Telenursery,” a program linking regional perinatal centers with a large academic neonatal practice through real‐time teleconferencing, in addition to providing weekly educational conferences 45 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified six studies that evaluated interventions to improve healthcare quality for neonates in community hospitals; two involved telemedicine 43‐48 . Hall et al described “Telenursery,” a program linking regional perinatal centers with a large academic neonatal practice through real‐time teleconferencing, in addition to providing weekly educational conferences 45 .…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, Sable et al found that a videoconferencing system for cardiologists from an academic center to guide care in a community setting provided diagnostic services more quickly (28 minutes vs 12 hours) and had high diagnostic accuracy 47 . The remaining four studies evaluated heterogeneous interventions such as a maternal education program to reduce shaking injuries to infants or implementation of evidence‐based order sets to reduce early onset group B streptococcal disease in neonates 43,44,46,48 . Five of the six neonatal studies demonstrated improved quality outcomes after intervention 43‐47 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective compliance strategies have been described in large university-affiliated centers, 7 community hospitals without academic affiliation 8 and in health maintenance organizations. 9 Systemwide factors that contributed to successful implementation of a GBS prevention protocol included: physician-leaders as catalysts for protocol presentation and implementation, provider education through meetings and mass mailings, and preprinted order forms that specifically address GBS colonization and antibiotic prophylaxis.…”
mentioning
confidence: 99%